SAT0075 Validation of The Rheumatoid Arthritis Prediction Rules for The Disease Development in Patients with Joint Pain from West Sweden. (15th July 2016) - Pullerits, R.; Bratt, S.; Turkkila, M.; Erlandsson, M.; Bokarewa, M.
Abstract : Background: Rheumatoid arthritis (RA) is a joint destructive disease, which leads to physical disability. There is no cure of RA today. Thus, recognition of RA at preclinical stages is essential for successful treatment. Objectives: To validate and improve known prediction rules aiming at early recognition of clinically suspect arthralgia and diagnosis of RA. Methods: Medical records of 241 first-time patients with clinically suspect joint pain were evaluated for RA diagnosis by the 2010 EULAR/ACR criteria (1) and by the RA prediction rules (13-points, Amsterdam (2)); and 16-points clinical assessment (Leiden (3)) and prospectively followed during 29–47 months. All the patients were a part of the inception cohort of 5455 patients whose samples were tested for RF and/or ACPA during 12 consecutive months at the Laboratory of Clinical Immunology at the University Hospital of Gothenburg. Patients with known diagnosis of RA, other rheumatic disease and chronic pain conditions were excluded. The utility of arthritis-specific autoantibody status (ACPA and/or RF) and the family history for RA prediction were analyzed. Results: The RA criteria applied to the records of the first visit identified 24% of patients as RA (EULAR score mean 7.6), 30% as undifferentiated arthritis (UA, EULAR score mean 3.6), while the remaining 45% of the patients were characterized as arthralgia (EULAR score mean 2.3). The 13-point and 16-point prediction rules allocated RA patients to the high-risk group with comparable sensitivity of 78% and 91%. The significant correlation between the two models was present in UA (r=0.398; p=0.0005) and arthralgia (r=0.411; p<0.0001) groups, but not in RA (r=0.0007, ns). Specificity for RA diagnosis at the first visit was higher in the 13-point rule (90.5%), however it was not discriminative between the arthralgia and UA groups. The clinical 16-point assessment discriminated successfully between RA/UA and between UA/arthralgia groups. The 16-point assessment allocated 50% of patients with UA to the high-risk group, which affected specificity. During the follow-up period, 23 cases of new RA and 5 UA were registered. The sensitivity of the 16-point assessment at the first visit was 60%, similar for the antibody-positive and for antibody–negative cases. The sensitivity of the 13-point rule was 21% (p=0.003), and was selective for the antibody-positive cases. At the first visit, subjects with family history of RA were over-represented in the arthralgia group (p=0.022). At follow-up only 1 of them developed UA. Conclusions: Both prediction rules are shown to be sensitive identify RA patients at assessment. The clinical 16-point assessment has prospective sensitivity for new cases. This is shown independently of autoantibody status and family history of RA. References: Cader MZ et al. Performance of the 2010 ACR/EULAR criteria for rheumatoid arthritis: comparison with 1987 ACR criteria in a very early synovitis cohortAnn Rheum Dis. 2011;70:949–55. van de Stadt LA et al. A prediction rule for the development of arthritis in seropositive arthralgia patients. Ann Rheum Dis. 2013;72:1920–6. Krabben A et al. Risk of RA development in patients with unclassified arthritis according to the 2010 ACR/EULAR criteria for RA. Rheumatology (Oxford). 2013;52:1265–70. Disclosure of Interest: None declared